Insights into the glioblastoma tumor microenvironment: current and emerging therapeutic approaches - Tripathy, Dev Kumar; Panda, Lakshmi Priya; Biswal, Suryanarayan; Barhwal, Kalpana (Frontiers in Pharmacology, 2024)
Glioblastoma (GB) is an intrusive and recurrent primary brain tumor with low survivability. The heterogeneity of the tumor microenvironment plays a crucial role in the stemness and proliferation of GB. The tumor microenvironment induces tumor heterogeneity of cancer cells by facilitating clonal evolution and promoting multidrug resistance, leading to cancer cell progression and metastasis. It also plays an important role in angiogenesis to nourish the hypoxic tumor environment. There is a strong interaction of neoplastic cells with their surrounding microenvironment that comprise several immune and non-immune cellular components. The tumor microenvironment is a complex network of immune components like microglia, macrophages, T cells, B cells, natural killer (NK) cells, dendritic cells and myeloid-derived suppressor cells, and non-immune components such as extracellular matrix, endothelial cells, astrocytes and neurons. The prognosis of GB is thus challenging, making it a difficult target for therapeutic interventions. The current therapeutic approaches target these regulators of tumor micro-environment through both generalized and personalized approaches. The review provides a summary of important milestones in GB research, factors regulating tumor microenvironment and promoting angiogenesis and potential therapeutic agents widely used for the treatment of GB patients.